The fragility of a structurally diverse duplication block triggers recurrent genomic amplification. Issue 1 (8th December 2020) - Suzuki, Ryusuke; Murata, Michael M; Manguso, Nicholas; Watanabe, Takaaki; Mouakkad-Montoya, Lila; Igari, Fumie; Rahman, Md Maminur; Qu, Ying; Cui, Xiaojiang; Giuliano, Armando E; Takeda, Shunichi; Tanaka, Hisashi
Abstract: The human genome contains hundreds of large, structurally diverse blocks that are insufficiently represented in the reference genome and are thus not amenable to genomic analyses. Structural diversity in the human population suggests that these blocks are unstable in the germline; however, whether or not these blocks are also unstable in the cancer genome remains elusive. Here we report that the 500 kb block called KRTAP_region_1 ( KRTAP-1 ) on 17q12–21 recurrently demarcates the amplicon of the ERBB2 (HER2) oncogene in breast tumors. KRTAP-1 carries numerous tandemly-duplicated segments that exhibit diversity within the human population. We evaluated the fragility of the block by cytogenetically measuring the distances between the flanking regions and found that spontaneous distance outliers (i.e DNA breaks) appear more frequently at KRTAP-1 than at the representative common fragile site (CFS) FRA16D. Unlike CFSs, KRTAP-1 is not sensitive to aphidicolin. The exonuclease activity of DNA repair protein Mre11 protects KRTAP-1 from breaks, whereas CtIP does not. Breaks at KRTAP-1 lead to the palindromic duplication of the ERBB2 locus and trigger Breakage-Fusion-Bridge cycles. Our results indicate that an insufficiently investigated area of the human genome is fragile and could play a crucial role in cancer genome evolution.